PROFESSIONAL ETHICS OF TRANSLATORS IN THE FIELD OF PROFESSIONAL COMMUNICATION FOR THE DEAF (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: This article is dedicated to the ethics and norms of translation, particularly sign language translation. Virtually every type of work has professional norms, the violation of which leads to numerous conflict situations. These issues are precisely what professional ethics and the professional code of ethics address, representing a set of norms and rules of conduct for a specific professional group, which ensures the moral nature of relationships conditioned by or associated with professional activities.